Integrating artificial intelligence with the Internet of Things for state-of-the-art medical care systems - Fahmy, Khadeja; Zorkany, Mohammed; Ammar, Abd El-Hady (Review of Computer Engineering Research, 2025)
The goal of this study is to investigate the AIoT the integration of artificial intelligence (AI) and the Internet of Things (IoT) in healthcare systems and to create a thorough research plan that will look at different machine learning approaches in IoT-based e-health systems. Using a survey-based methodology, this study independently investigates the current uses of machine learning and the Internet of Things in the healthcare industry. It emphasizes how effective these technologies are and how integrating AIoT could lead to benefits. Initial results show that although AI and IoT work well together in a variety of IT applications, their combination in healthcare with AIoT offers more potential. In order to enhance continuous monitoring of data and decision-making procedures in e-health systems, the study identifies important gaps and opportunities for developing machine learning algorithms. With an emphasis on overcoming obstacles and seizing opportunities to maximize e-health systems, the knowledge gathered from this study can direct future advancements in AIoT for healthcare. For IT developers and healthcare experts hoping to successfully deploy AIoT systems, this will have real-world repercussions.